First Isolation and Characterization of Feline Panleukopenia Virus From Wild Raccoon Dogs in the Residential Area of Shanghai, China - Chen Chen; Jin Tao; Ling Tang; Tong Sun; Zhuyun Sun; Huan Xu; Shuaitao Deng; Cheng Xue; Xing Ji; Rui Wang; Hongjun Chen (Veterinary Medicine and Science)
ABSTRACT Background Carnivore parvovirus is commonly detected in canines and felines and results in a range of symptoms, including diarrhoea, with a high lethality rate. In recent years, the gradual restoration of urban ecosystems coupled with a lack of natural predators means that wild raccoon dogs have gradually entered residential neighbourhoods in Shanghai, and the carnivore parvovirus carried by such canines may seriously affect their health and that of dogs and cats in these neighbourhoods. Objectives Therefore, it is essential to monitor wild raccoon dogs for carnivore parvovirus. Methods The wild raccoon samples were collected from the residential area of Shanghai and screened for parvovirus, followed by virus isolation and sequence comparison analysis. Results In this study, three strains of parvovirus, YSH1‐2022, YSH2‐2022 and GSW1‐2023, were isolated from anal and pharyngeal swab mixtures of 42 live raccoon dogs and two dead raccoon dogs in Shanghai, China. After alignment, it was found that the three strains of parvovirus were all located in the same branch as feline panleukopenia virus (FPV), and the three VP2 genes had 100% homology with FPV VP2 genes isolated from Shanghai and Yangzhou, Jiangsu Province. The homology of the three NS1 genes with FPV NS1 isolated from Shanghai and other places was 99.9%–100%. Conclusion This is the first report of FPV isolated from raccoon dogs. In this study, the host range and risk of infection of parvovirus were evaluated, providing data to support wildlife management and policy formulation in Shanghai.